ENVIRONMENTAL ORIENTATION IN TURTLE CONSERVATION AREA IN BANTUL REGENCY - Debora S. Purba; April Sabdi Marbun (CERED Indonesia Institute, 2020)
Developing a conservation area within tourist attraction area requires conservation awareness of flora and fauna. The stakeholders take an important part to actualize the area to achieve a balance ecosystem. Thus, the knowledge, the expertise, the ethics of conservation are required for developing and managing this area. This study aims to examine the environmental orientation of stakeholders in Pantai Goa Cemara where is the coastal tourist area of Bantul that becomes has a turtle conservation area. Environmental orientation is a point of view of the stakeholder that underlying the mindset, the attention, the tendency through physical environment like nature and social environment (for example society and culture) and there are four orientations: instrumental, territorial, sentimental, and symbolic. Utilizing depth interview to the stakeholders, this research found that stakeholders of Pantai Goa Cemara do not have all of four the environmental orientations. There are several tendencies in each environmental orientation but it is not firm sufficiently to find that each stakeholder is attached to one of the four orientations. It affects the stakeholders that has not become effective and efficient in realizing and supporting Pantai Goa Cemara as turtle conservation area in Bantul Regency.